Inhibition of DNM1L and mitochondrial fission attenuates inflammatory response in fibroblast‐like synoviocytes of rheumatoid arthritis. Issue 2 (21st November 2019) - Wang, Xiaoyan; Chen, Zhufeng; Fan, Xuemei; Li, Wei; Qu, Jiaqi; Dong, Chuan; Wang, Zhixue; Ji, Zhenwei; Li, Yang
Abstract: Mitochondrial fission and fusion are important for mitochondrial function, and dynamin 1‐like protein (DNM1L) is a key regulator of mitochondrial fission. We investigated the effect of mitochondrial fission on mitochondrial function and inflammation in fibroblast‐like synoviocytes (FLSs) during rheumatoid arthritis (RA). DNM1L expression was determined in synovial tissues (STs) from RA and non‐RA patients. FLSs were isolated from STs and treated with a DNM1L inhibitor (mdivi‐1, mitochondrial division inhibitor 1) or transfected with DNM1L ‐specific siRNA. Mitochondrial morphology, DNM1L expression, cell viability, mitochondrial membrane potential, reactive oxygen species (ROS), apoptosis, inflammatory cytokine expression and autophagy were examined. The impact of mdivi‐1 treatment on development and severity of collagen‐induced arthritis (CIA) was determined in mice. Up‐regulated DNM1L expression was associated with reduced mitochondrial length in STs from patients with RA and increased RA severity. Inhibition of DNM1L in FLSs triggered mitochondrial depolarization, mitochondrial elongation, decreased cell viability, production of ROS, IL‐8 and COX‐2, and increased apoptosis. DNM1L deficiency inhibited IL‐1β–mediated AKT/IKK activation, NF‐κBp65 nuclear translocation and LC3B‐related autophagy, but enhanced NFKBIA expression. Treatment of CIA mice with mdivi‐1 decreased disease severity by modulating inflammatory cytokine and ROS production. Our major results are that up‐regulated DNM1L and mitochondrial fission promoted survival, LC3B‐related autophagy and ROS production in FLSs, factors that lead to inflammation by regulating AKT/IKK/NFKBIA/NF‐κB signalling. Thus, inhibition of DNM1L may be a new strategy for treatment of RA.